The Concept of the Term Sawa’ (Common Word) in the Qur’an According to Fakhruddin al-Razi in Tafsir Mafatih al-Ghaib - Diaz Supandi, Muhammad (Noor: Journal of Islamic Studies, 2025)
Religious pluralism is a complex issue in modern society that acknowledges religious diversity and the view that each religion has its own truth. Among Muslims, understanding pluralism without compromising faith principles poses a significant challenge. The concept of Kalimat Sawa’ (Common Word) from Surah Ali Imran: 64, proposed by Prophet Muhammad ﷺ to the People of the Book, is relevant in this context. Kalimat Sawa’ calls for the oneness of Allah and avoidance of associating partners with Him, providing a basis for fair interfaith dialogue. This study employs a quantitative approach with a comparative analysis of Tafsir Mafatih al-Ghaib by Fakhruddin al-Razi and other commentaries, and utilizes digital sources to expand the scope of data. The findings indicate that Kalimat Sawa’ emphasizes justice and equality in interfaith dialogue and the importance of returning to the principle of monotheism. Although deeply rooted in the socio-historical context of al-Razi, this concept must be adapted to digital dynamics and contemporary pluralism to remain relevant. In conclusion, Kalimat Sawa’ offers a framework for fostering harmonious relationships amid religious diversity by emphasizing dialogue based on justice. However, its application needs to be adjusted to contemporary contexts to address the increasingly complex challenges of religious pluralism and contribute to interfaith harmony.